A high abrasion resistant flux cored wire for electric arc additive manufacturing and a method of making the same

CN122829466APending Publication Date: 2026-09-29SHANGHAI UNIV OF ENG SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610887005.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

[0006]针对现有技术中耐磨药芯焊丝存在的耐磨性能不足、韧性与耐磨性难以兼顾等缺陷,本发明的主要目的是提供一种用于电弧增材制造的高耐磨药芯焊丝,通过科学调控各合金元素的配比,实现各元素的协同作用,显著提升熔敷金属的硬度、耐磨性和韧性,满足工业重载磨损工况的使用需求,特别是应用于矿山机械、冶金设备、水泥机械等承受重度磨粒磨损、冲击磨损的零部件的堆焊修复与表面强化,可显著提升零部件的服役寿命

Benefits of technology

[0028](1)耐磨性能优异:本发明通过科学配比C、Cr、Mo、W、V等元素,形成多种高硬度碳化物,这些碳化物均匀分布于基体中,协同提升熔敷金属的硬度和耐磨性,经测试本发明的高耐磨药芯焊丝熔敷金属硬度可达61-66HRC。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a high wear-resistant flux-cored wire for electric arc additive manufacturing and a preparation method thereof, and belongs to the technical field of welding materials. The high wear-resistant flux-cored wire has the following chemical components in percentage by weight: C: 0.6%-1.0%, Si: 0.5%-0.8%, Mn: 0.6%-1.0%, Mo: 4.5%-6.0%, Ni: 1.0%-1.5%, Cr: 3.2%-5.0%, W: 5.5%-6.5%, V: 2.5%-4.0%, Co: 0.4%-0.6%, Nb: 0.2%-0.5%, B: 0.01%-0.05%, and the balance of Fe and inevitable impurities. The application forms an atypical carbide system through the alloy components of high-content Mo, W and V and low-content Cr synergistic effect, avoids the traditional Cr7C3 dominant shift to the M2C, M6C and VC composite system, and effectively improves the hardness and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of welding materials technology, specifically relating to a high wear-resistant flux-cored welding wire for arc additive manufacturing and its preparation method. Background Technology

[0002] Wafer-Arc Additive Manufacturing (WAAM), a key branch of metal additive manufacturing, is an advanced digital manufacturing technology that uses an electric arc as a heat source to directly manufacture near-net-shape metal parts through layer-by-layer cladding deposition of filaments. Compared to laser and electron beam additive manufacturing, WAAM technology boasts significant advantages such as high deposition efficiency, low equipment cost, high filament utilization, and the ability to manufacture large components. It shows broad application prospects in the manufacturing and repair of highly wear-resistant parts in fields such as mining machinery, metallurgical equipment, engineering machinery, and energy equipment. Wear-resistant parts are subjected to complex conditions such as abrasive wear, impact wear, and high-temperature wear, placing stringent requirements on the material's hardness, wear resistance, crack resistance, high-temperature stability, and microstructure uniformity. Traditional manufacturing processes (casting, forging, and machining) suffer from low material utilization, long production cycles, difficulty in forming complex structures, and large subsequent machining allowances. Furthermore, they struggle to balance high hardness and high toughness, resulting in short component lifespans, frequent replacements, and significantly increased equipment maintenance costs. The emergence of arc additive manufacturing technology provides a new path to solve the above problems. Wire is the core raw material of WAAM technology, and its composition design, metallurgical properties, and manufacturing process directly determine the forming quality, microstructure, and service life of additive components. Flux-cored welding wire is the preferred wire type for WAAM technology. It consists of a metal strip outer sheath and an inner flux powder core, combining the metallurgical control function of electrode coating with the continuous wire feeding advantage of solid welding wire.

[0003] In recent years, extensive research has been conducted both domestically and internationally on flux-cored welding wires for arc additive manufacturing, and some progress has been made. In terms of composition design, existing wear-resistant flux-cored welding wires are mostly iron-based, with added alloying elements such as Cr, Mn, Si, Ni, Mo, and W, combined with hard phases such as WC, Cr3C2, TiC, and NbC to improve wear resistance. For example, patent document CN107138874A discloses a hypereutectic iron-chromium-carbon-titanium-niobium-nitrogen-lanthanum aluminate flux-cored welding wire, which improves wear resistance through high carbon and high chromium composition design and carbide reinforcement; patent document CN121988931A uses a FeCrNiMoW high-entropy alloy matrix and introduces a (Nb,Ti)C carbide reinforcing phase to balance toughness and high-temperature wear resistance; patent document CN120326205A from Suzhou Weiaode Welding Materials Technology Co., Ltd. designs a three-layer flux-cored structure, with the inner layer containing chromium carbide and recycled slag, and the outer layer containing tungsten carbide, improving wear resistance by 20%-30% through gradient composition design. In terms of manufacturing process, the existing flux-cored welding wire manufacturing mainly includes steel strip pretreatment, batching and mixing, powder filling, rolling and forming, drawing, and heat treatment. The core control indicators are flux filling rate, composition uniformity, welding wire dimensional accuracy, and surface quality. To improve performance, researchers have continuously optimized the preparation process, such as using ultrasonic dispersion and mixing to improve the uniformity of the powder, layered vibration compaction to reduce porosity, multi-pass cold drawing to improve the density of the welding wire, and low-temperature annealing to eliminate processing stress, which effectively reduces defects in welding wire preparation and improves process stability.

[0004] Despite some advancements in existing technologies, current high-wear-resistant flux-cored welding wires for arc additive manufacturing still face numerous challenges. Their composition design is often flawed, making it difficult to balance wear resistance with toughness. Existing wear-resistant flux-cored welding wires primarily enhance wear resistance by adding a single high-hardness hard phase (such as WC or Cr3C2). However, excessively high hard phase content can lead to increased brittleness and decreased crack resistance in the weld metal, resulting in defects such as cracks and spalling during additive manufacturing. Conversely, insufficient hard phase content results in inadequate wear resistance, failing to meet the demands of heavy-duty wear-resistant applications. Furthermore, the hard phase exhibits weak interfacial bonding with the matrix, leading to easy detachment and failure. In existing flux-cored welding wires, the hard phase is often a directly added pre-formed particle, mechanically bonded to the iron matrix, resulting in low interfacial bonding strength. In the high-temperature molten pool environment of an electric arc, hard phase particles are prone to dissolution, oxidation, agglomeration, or flotation, leading to uneven distribution and coarse particle size in the weld metal, and making the interface with the matrix susceptible to crack initiation. Under abrasive wear and impact loads, hard phase particles are prone to detach from the matrix, losing the support of the wear-resistant skeleton, leading to a sharp increase in the material wear rate and a shortened component service life. Simultaneously, coarse carbides easily induce stress concentration, reducing the material's impact toughness and fatigue resistance, making it difficult to adapt to high-impact wear conditions. Furthermore, traditional heat treatment processes often involve a single high-temperature annealing, which can easily lead to the decomposition of flux-cored components, segregation of alloying elements, and coarsening of carbides, reducing the performance of the welding wire.

[0005] Therefore, developing a wear-resistant flux-cored welding wire with a reasonable composition design, good flux uniformity, strong bonding between the hard phase and the matrix interface, and simple and stable preparation process, and optimizing its preparation method, is of great practical significance and engineering value for improving the performance and quality of wear-resistant components manufactured by arc additive manufacturing and promoting the industrial application of WAAM technology in the field of wear resistance. Summary of the Invention

[0006] To address the shortcomings of existing wear-resistant flux-cored welding wires, such as insufficient wear resistance and difficulty in achieving both toughness and wear resistance, the main objective of this invention is to provide a high-wear-resistant flux-cored welding wire for arc additive manufacturing. By scientifically controlling the proportions of various alloying elements, the synergistic effect of each element is achieved, significantly improving the hardness, wear resistance, and toughness of the deposited metal. This meets the usage requirements of heavy-duty wear conditions in industrial applications, and is particularly suitable for the surfacing repair and surface strengthening of components subjected to severe abrasive and impact wear, such as those in mining machinery, metallurgical equipment, and cement machinery, significantly extending the service life of these components.

[0007] Another object of the present invention is to provide a method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing, which is simple in process and easy to industrialize.

[0008] One object of the present invention is to provide the application of the high wear-resistant flux-cored welding wire for arc additive manufacturing in the welding repair and surface strengthening of parts for mining machinery, metallurgical equipment, and cement machinery in arc additive manufacturing.

[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0010] In a first aspect, the present invention provides a high wear-resistant flux-cored welding wire for arc additive manufacturing, the chemical composition by weight percentage being: C: 0.6%-1.0%, Si: 0.5%-0.8%, Mn: 0.6%-1.0%, Mo: 4.5%-6.0%, Ni: 1.0%-1.5%, Cr: 3.2%-5.0%, W: 5.5%-6.5%, V: 2.5%-4.0%, Co: 0.4%-0.6%, Nb: 0.2%-0.5%, B: 0.01%-0.05%, with the balance being Fe and unavoidable impurities.

[0011] Preferably, the weight of Cr and Mo-W satisfies: Cr / (Mo+W) = 0.26-0.45.

[0012] As a preferred option, the contents of V and Nb satisfy the following: V+Nb=3.0-4.2, B / Nb=0.06-0.15.

[0013] In a second aspect of the present invention, the method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing includes the following steps:

[0014] (1) Core material preparation: According to the above requirements for chemical composition of the deposited metal, calculate and weigh each alloy powder, put each raw material into the powder mixer, mix evenly, and obtain core mixture;

[0015] (2) Drying: Place the drug core mixture into a drying oven to remove moisture;

[0016] (3) Steel strip forming: The low carbon steel strip is placed in the forming machine and rolled into a U-shaped groove. The width and depth of the U-shaped groove are controlled to match the filling amount of the core.

[0017] (4) Core filling: The core mixture dried in step (2) is evenly filled into the U-shaped groove;

[0018] (5) Closing and drawing: Close the U-shaped groove filled with flux-cored mixture, roll it into an O-shape, and then draw it step by step with a wire drawing machine until it reaches the preset welding wire diameter;

[0019] (6) Finishing and surface treatment: After the welding wire is drawn, it is ultrasonically cleaned to remove oil and mechanically straightened to eliminate surface oil and internal stress, and then vacuum packaged.

[0020] Preferably, in step (1), during the mixing process, the speed of the mixer is controlled to be 200-300 r / min and the mixing time is 30-60 min.

[0021] Preferably, in step (2), the drying temperature is 120-150℃ and the drying time is 2-3 h.

[0022] Preferably, in step (3), the low-carbon steel strip has a carbon content of ≤0.15%, a thickness of 0.6-1.0 mm, and a width of 12-16 mm.

[0023] Preferably, in step (4), the core filling rate is controlled to be 25%-35%.

[0024] Preferably, in step (5), the drawing speed is 5-8 m / min and the preset welding wire diameter is 1.2-1.6 mm.

[0025] Preferably, in step (6), the ultrasonic frequency is 25-40 KHZ and the water temperature for ultrasonic cleaning is 30-45℃.

[0026] A third aspect of the present invention also provides the application of the high wear-resistant flux-cored welding wire for arc additive manufacturing in the welding repair and surface strengthening of parts for mining machinery, metallurgical equipment, and cement machinery manufactured by arc additive manufacturing.

[0027] Compared with existing technologies, this invention forms an atypical carbide system by designing an alloy composition with high Mo, W, and V content and low Cr content to achieve synergistic effects. This avoids the traditional Cr7C3-dominated system and shifts to an M2C, M6C, and VC composite system, effectively improving hardness and wear resistance. It has at least the following beneficial effects:

[0028] (1) Excellent wear resistance: This invention forms a variety of high-hardness carbides by scientifically proportioning elements such as C, Cr, Mo, W, and V. These carbides are evenly distributed in the matrix, which synergistically improves the hardness and wear resistance of the weld metal. According to the test, the hardness of the weld metal of the high wear-resistant flux-cored welding wire of this invention can reach 61-66 HRC.

[0029] (2) Strength, toughness and crack resistance: Ni stabilizes austenite, improves matrix toughness, reduces crack sensitivity, and improves low temperature and dynamic impact toughness; Nb forms fine NbC, which strongly refines grains, purifies grain boundaries, and inhibits carbide coarsening, significantly improving strength, toughness and anti-stripping ability; Co further improves carbides, improves microstructure uniformity and high temperature toughness, and Ni, Nb and Co synergistically significantly improve toughness and crack resistance.

[0030] (3) Wide range of applications: The high wear-resistant flux-cored welding wire of the present invention can be widely used in the welding repair and surface strengthening of parts in mining machinery, metallurgical equipment, cement machinery, engineering machinery and other fields. It is especially suitable for working conditions that are subjected to heavy abrasive wear and impact wear, such as crusher liners, rollers, grinding rollers, bucket teeth and other parts. Detailed Implementation

[0031] To more fully understand and demonstrate the technical solutions, objectives, and advantages of the present invention, the technical effects produced by the present invention will be further described in detail and completely below with reference to specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. It should be noted that other embodiments obtained by those skilled in the art without departing from the concept of the present invention are all within the protection scope of the present invention.

[0032] Example 1

[0033] This embodiment provides a high wear-resistant flux-cored welding wire for arc additive manufacturing. The mass percentage of each element in the welding wire is as follows: C: 0.6%, Si: 0.5%, Mn: 0.6%, Mo: 4.5%, Ni: 1.2%, Cr: 3.2%, W: 5.5%, V: 2.5%, Co: 0.4%, Nb: 0.4%, B: 0.02%, with the balance being Fe and unavoidable impurity elements.

[0034] Example 2

[0035] This embodiment provides a high wear-resistant flux-cored welding wire for arc additive manufacturing. The mass percentage of each element in the welding wire is as follows: C: 0.8%, Si: 0.65%, Mn: 0.8%, Mo: 5.2%, Ni: 1.1%, Cr: 4.0%, W: 5.8%, V: 3.2%, Co: 0.5%, Nb: 0.5%, B: 0.03%, with the balance being Fe and unavoidable impurity elements.

[0036] Example 3

[0037] This embodiment provides a high wear-resistant flux-cored welding wire for arc additive manufacturing. The mass percentage of each element in the welding wire is as follows: C: 1.0%, Si: 0.8%, Mn: 1.0%, Mo: 5.6%, Ni: 1.4%, Cr: 4.5%, W: 6.5%, V: 3.5%, Co: 0.55%, Nb: 0.3%, B: 0.05%, with the balance being Fe and unavoidable impurity elements.

[0038] Example 4

[0039] This embodiment provides a high wear-resistant flux-cored welding wire for arc additive manufacturing. The mass percentage of each element in the welding wire is as follows: C: 0.9%, Si: 0.7%, Mn: 0.9%, Mo: 4.8%, Ni: 1.25%, Cr: 4.2%, W: 6.0%, V: 2.8%, Co: 0.45%, Nb: 0.4%, B: 0.04%, with the balance being Fe and unavoidable impurity elements.

[0040] Example 5

[0041] This embodiment provides a high wear-resistant flux-cored welding wire for arc additive manufacturing. The mass percentage of each element in the welding wire is as follows: C: 0.7%, Si: 0.6%, Mn: 1.0%, Mo: 5.5%, Ni: 1.4%, Cr: 4.4%, W: 5.85%, V: 3.25%, Co: 0.58%, Nb: 0.48%, B: 0.035%, with the balance being Fe and unavoidable impurity elements.

[0042] The high wear-resistant flux-cored welding wires prepared in Examples 1-5 for arc additive manufacturing, along with conventional commercially available wear-resistant welding wires (comparative Example 1 and Comparative Example 2, models YD212 and YD405, respectively), were all subjected to gas metal arc welding (GMAW). The shielding gas was 80% Ar + 20% CO2, the base material was Q235 steel, and the welding parameters were: arc current of 180 A, arc voltage of 22 V, wire feed speed of 7.9 m / min, and welding speed of 380 mm / min. The Rockwell hardness was measured using an HR-150 Rockwell hardness tester with a load of 1.5 kN held for 15 s. Abrasive wear tests were performed using an MLS-255 wet sand rubber wheel abrasion tester.

[0043] Table 1

[0044]

[0045] As shown in Table 1, the Rockwell hardness of samples 1-5 in all examples is ≥61 HRC, and the coefficient of friction is ≥0.36; while the Rockwell hardness of samples 1 and 2 in comparative examples is only 54 HRC and 52 HRC, respectively, and the coefficients of friction are 0.28 and 0.26, respectively. Compared with the comparative examples, the samples in each example have significant advantages in both Rockwell hardness and coefficient of friction, and the overall mechanical and frictional properties are significantly improved. This proves that the high wear-resistant flux-cored welding wire used in arc additive manufacturing in this invention forms an atypical carbide system by designing an alloy composition with high Mo, W, and V content and low Cr content working synergistically. This avoids the traditional Cr7C3-dominated system and shifts to an M2C, M6C, and VC composite system, effectively improving hardness and wear resistance. Its application in arc additive manufacturing parts, such as welding repair and surface strengthening of parts in mining machinery, metallurgical equipment, and cement machinery, has broad application prospects.

[0046] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A high wear-resistant flux-cored welding wire for arc additive manufacturing, characterized in that, Its chemical composition by weight percentage is as follows: C: 0.6%-1.0%, Si: 0.5%-0.8%, Mn: 0.6%-1.0%, Mo: 4.5%-6.0%, Ni: 1.0%-1.5%, Cr: 3.2%-5.0%, W: 5.5%-6.5%, V: 2.5%-4.0%, Co: 0.4%-0.6%, Nb: 0.2%-0.5%, B: 0.01%-0.05%, with the balance being Fe and unavoidable impurities.

2. The high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 1, characterized in that, The weights of Cr and Mo-W satisfy: Cr / (Mo+W) = 0.26-0.

45.

3. The high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 1, characterized in that, The contents of V and Nb satisfy the following: V + Nb = 3.0-4.2, B / Nb = 0.06-0.

15.

4. The method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Core material preparation: According to the above requirements for chemical composition of the deposited metal, calculate and weigh each alloy powder, put each raw material into the powder mixer, mix evenly, and obtain core mixture; (2) Drying: Place the drug core mixture into a drying oven to remove moisture; (3) Steel strip forming: The low carbon steel strip is placed in the forming machine and rolled into a U-shaped groove. The width and depth of the U-shaped groove are controlled to match the filling amount of the core. (4) Core filling: The core mixture dried in step (2) is evenly filled into the U-shaped groove; (5) Closing and drawing: Close the U-shaped groove filled with flux-cored mixture, roll it into an O-shape, and then draw it step by step with a wire drawing machine until it reaches the preset welding wire diameter; (6) Finishing and surface treatment: After the welding wire is drawn, it is ultrasonically cleaned to remove oil and mechanically straightened to eliminate surface oil and internal stress, and then vacuum packaged.

5. The method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 4, characterized in that, In step (1), the speed of the mixer is controlled at 200-300 r / min and the mixing time is 30-60 min during the mixing process.

6. The method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 4, characterized in that, In step (2), the drying temperature is 120-150℃ and the drying time is 2-3 h.

7. The method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 4, characterized in that, In step (3), the carbon content of the low-carbon steel strip is ≤0.15%, the thickness is 0.6-1.0 mm, and the width is 12-16 mm.

8. The method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 4, characterized in that, In step (4), the core filling rate is controlled to be 25%-35%.

9. The method for preparing the high wear-resistant flux-cored welding wire for arc additive manufacturing according to claim 4, characterized in that, In step (5), the drawing speed is 5-8 m / min, and the preset welding wire diameter is 1.2-1.6 mm; In step (6), the ultrasonic frequency is 25-40 KHZ and the water temperature for ultrasonic cleaning is 30-45℃.

10. The application of the high wear-resistant flux-cored welding wire for arc additive manufacturing as described in any one of claims 1 to 3 in the surfacing repair and surface strengthening of parts for mining machinery, metallurgical equipment, and cement machinery manufactured by arc additive manufacturing.

Citation Information

Patent Citations

  • Hypereutectic iron-chromium-carbon-titanium-niobium-nitrogen-lanthanum aluminate flux-cored wire for arc surfacing additive manufacturing

    CN107138874A

  • Wear-resistant flux-cored wire and manufacturing method thereof

    CN120326205A

  • FeCrNiMoW-based high-entropy alloy hardfacing flux-cored wire and preparation method thereof

    CN121988931A